Chemical synthesis of the pentasaccharide repeating unit of the O-specific polysaccharide from Escherichia coli O132 in the form of its 2-aminoethyl glycoside - Pal, Debasish; Mukhopadhyay, Balaram (Beilstein Journal of Organic Chemistry, 2019)
The total chemical synthesis of the pentasaccharide repeating unit of the O-polysaccharide from E. coli O132 is accomplished in the form of its 2-aminoethyl glycoside. The 2-aminoethyl glycoside is particularly important as it allows further glycoconjugate formation utilizing the terminal amine without affecting the stereochemistry of the reducing end. The target was achieved through a [3 + 2] strategy where the required monosaccharide building blocks are prepared from commercially available sugars through rational protecting group manipulation. The NIS-mediated activation of thioglycosides was used extensively for the glycosylation reactions throughout.
Keywords: 2-aminoethyl glycoside; diarrhea; galactofuranose; O-specific polysaccharide; total synthesis

(untitled) - Larue, K.; Kimber, M. S.; Ford, R.; Whitfield, C. (J. Biol. Chem., 2009)

(untitled) - Beutin, L.; Wang, Q.; Naumann, D.; Han, W.; Krause, G.; Leomil, L.; Wang, L.; Feng, L. (J. Med. Microbiol., 2007)

(untitled) - Blanco, J. E.; Blanco, M.; Mora, A.; Jansen, W. H.; Garcı́a, V.; Vázquez, M. L.; Blanco, J. (Vet. Microbiol., 1998)

(untitled) - Peruski, L. F., Jr; Kay, B. A.; El-Yazeed, R. A.; El-Etr, S. H.; Cravioto, A.; Wierzba, T. F.; Rao, M.; ElGhorab, N.; Shaheen, H.; Khalil, S. B.; Kamal, K.; Wasfy, M. O.; et al. (J. Clin. Microbiol., 1999)

(untitled) - Aidar-Ugrinovich, L.; Blanco, J.; Blanco, M.; Blanco, J. E.; Leomil, L.; Dahbi, G.; Mora, A.; Onuma, D. L.; Silveira, W. D.; Pestana de Castro, A. F. (Int. J. Food Microbiol., 2007)

(untitled) - Penteado, A. S.; Ugrinovich, L. A.; Blanco, J.; Blanco, M.; Blanco, J. E.; Mora, A.; Andrade, J. R. C.; Corrêa, S. S.; Pestana de Castro, A. F. (Vet. Microbiol., 2002)

(untitled) - Shashkov, A. S.; Zhang, W.; Perepelov, A. V.; Weintraub, A.; Liu, B.; Widmalm, G.; Knirel, Y. A. (Carbohydr. Res., 2016)

(untitled) - Mitra, A.; Mukhopadhyay, B. (Eur. J. Org. Chem., 2019)

(untitled) - Adak, A.; Mukhopadhyay, B. (Carbohydr. Res., 2019)

(untitled) - Sarkar, V.; Mukhopadhyay, B. (Carbohydr. Res., 2018)

(untitled) - Mandal, P. K. (Beilstein J. Org. Chem., 2014)

(untitled) - Dhara, D.; Kar, R. K.; Bhunia, A.; Misra, A. K. (Eur. J. Org. Chem., 2014)

(untitled) - Geng, X.; Wang, L.; Gu, G.; Guo, Z. (Carbohydr. Res., 2016)

(untitled) - Zemplén, G. (Ber. Dtsch. Chem. Ges. B, 1926)

(untitled) - Lu, L.-D.; Shie, C.-R.; Kulkarni, S. S.; Pan, G.-R.; Lu, X.-A.; Hung, S.-C. (Org. Lett., 2006)

(untitled) - Wang, L.; Overkleeft, H. S.; van der Marel, G. A.; Codée, J. D. C. (J. Am. Chem. Soc., 2018)

(untitled) - Limberg, G.; Thiem, J. (Carbohydr. Res., 1995)

(untitled) - Jacquinet, J.-C. (Carbohydr. Res., 2004)

(untitled) - Sato, K.-i.; Akai, S.; Sakai, K.; Kojima, M.; Murakami, H.; Idoji, T. (Tetrahedron Lett., 2005)

(untitled) - Tanaka, H.; Hamaya, Y.; Nishiwaki, N.; Ishida, H. (Carbohydr. Res., 2018)

(untitled) - Completo, G. C.; Lowary, T. L. (J. Org. Chem., 2008)

(untitled) - Lee, Y. J.; Lee, B.-Y.; Jeon, H. B.; Kim, K. S. (Org. Lett., 2006)

(untitled) - Mukhopadhyay, B.; Field, R. A. (Carbohydr. Res., 2003)

(untitled) - Mootoo, D. R.; Konradsson, P.; Udodong, U.; Fraser-Reid, B. (J. Am. Chem. Soc., 1988)

(untitled) - Konradsson, P.; Mootoo, D. R.; McDevitt, R. E.; Fraser-Reid, B. (J. Chem. Soc., Chem. Commun., 1990)

(untitled) - Kanie, O.; Crawley, S. C.; Palcic, M. M.; Hindsgaul, O. (Carbohydr. Res., 1993)

(untitled) - Mitra, A.; Mukhopadhyay, B. (Synthesis, 2015)

(untitled) - Medgyes, G.; Jerkovich, G.; Kuszmann, J.; Fügedi, P. (Carbohydr. Res., 1989)

(untitled) - Sarkar, V.; Mukhopadhyay, B. (ChemistrySelect, 2016)